LEGISLATIVE AND INSTITUTIONAL FRAMEWORK FOR MITIGATING PRICE INCREASES IN THE REPUBLIC OF ARMENIA - Manaseryan, Tatul (State and Law, 2020)
By initiating legislative changes that will lead to significant changes in prices forsocially significant goods, the government should develop measures to mitigate theeffects of inflation. The legal regulation of price stability, assessing the level of inflationand predicting its dynamics are of great importance, since they make it possible toassess the degree of damage caused by this phenomenon and to contribute to theimplementation of anti-inflationary measures. Inflation control in the Republic ofArmenia is regulated by the RA Law "On the Central Bank of the Republic ofArmenia", the RA Constitution and other legal acts. It is important that the powers ofthe State Commission for the Protection of Economic Competition be legally expandedin order to take more decisive measures in case of unjustified price increases in highlyconcentrated commodity markets and to provide appropriate proposals to curbinflation in case of problems.
Keywords: price increases, commodity markets, legislative regulation, economic competition, commodities of basic needs